Epidemiological characterization of human infection with H5N6 avian influenza - Li, Fengying; Sun, Zhou; Tao, Mingyong; Song, Kai; Wang, Zhe; Ren, Xiaobin (Frontiers in Public Health, 2024)
Background In recent years, there have been frequent reports of human infection with H5N6 avian influenza. However, the fundamental characteristics of the disease remain unclear. This paper conducts a systematic review to explore the epidemiological features of the disease, aiming to provide a foundation for epidemic prevention and control and to serve as a reference for clinical diagnosis. Method A systematic search was performed in PubMed, Web of Science, CNKI, Wanfang and gray literature up to November 15, 2023. All articles were about the epidemic features of the H5N6 subtype of avian influenza, written in English or Chinese. Results This review encompasses 24 documented outbreaks of human H5N6 avian influenza, exclusively reported in southern China. The age range of cases spanned from under 2 years old to 81 years old. The incubation period ranged from 1 to 13 days, with a mean of 4.3 days. Among the 24 cases, 22 individuals had a documented history of contact with poultry. Of the 23 cases with available prognosis data, 12 resulted in fatalities, yielding a significant fatality rate of 52.2%. A noteworthy observation is that all cases with a history of contact with sick and dead poultry resulted in fatalities, and the difference in fatality rates between this group and others was statistically significant (χ2 = 7.441, p = 0.014). This study identified a total of 888 close contacts, none of whom demonstrated infection. Conclusion This study represents a comprehensive summary of the epidemiological characteristics of human H5N6 avian influenza. Significantly, it sheds light on the incubation period of the disease and underscores a potential elevated risk of mortality among patients with a history of contact with sick and dead poultry.